Study On Teachers' Personal Qualities, Self-Development Skills - Mesrobyan, Vardine (Զանգակ հրատ.)
The article presents the results of an experimental study on teachers’ personal qualities, as well as their self-development abilities. The aim of the study is to find out the peculiarities of lecturers’ personal qualities and self-development. Among the lecturers the following personal factors have been found above the average: warmth, rule-consciousness, emotional stability, social boldness, abstractedness, openness to change. And the indicators of self- development are average for lecturers, which shows that lecturers are able to realize their own opportunities, to develop themselves for professional growth. And after the analysis of the questionnaire results, we can conclude that for the Armenian lecturers the actions taken for self-recognition are as follows: self-development, retraining, communication with their colleagues, they prefer to be professional. The lecturers of the psychological weakness considered the following qualities: kindness, sincerity, difficult to accept innovations, lack of language knowledge.
Keywords: Psychology